Marxism : with and beyond Marx - Bagchi,Kumar and Chatterjee,Amita Ed.; Bagchi, Amiya Kumar; Chatterjee, Amita (London: Routledge, 2014)
Contributed articles presented at the International Conference on 'Marxism: Marx and Beyond', organised by the Institute of Development Studies, Kolkata, in collaboration with Centre for Marxian Studies, Jadavpur University, held during March 22-24, 2012, at Kolkata.
Includes bibliographical references and index.
Keywords: Philosophy, Marxist -- Congresses